Does Low FEV1 in Addition to Fixed Ratio and/or Lower Limit of Normal of FEV1/FVC Improve Prediction of Mortality in COPD? The NHANES-III-linked-mortality Cohort - Odeyemi, Yewande E. (J Natl Med Assoc, 2018)
PURPOSE: There is presently an ongoing debate on the relative merits of suggested criteria for spirometric airway obstruction. This study tests the null hypothesis that no superiority exists with the use of fixed ratio (FR) of forced expiratory volume in the first second (FEV1)/forced vital capacity (FVC) < 0.7 versus less than lower limit predicted (LLN) criteria with or without FEV1 <80% predicted in regards to future mortality. METHODS: In 1988–1994 the Third National Health and Nutrition Examination Survey (NHANES III) measured FEV1 and FVC with mortality follow-up data through December 31, 2011. For this survival analysis 7472 persons aged 40 and over with complete data formed the analytic sample. RESULTS: There were a total of 3554 deaths. Weighted Cox proportional hazards regression revealed an increased hazard ratio in persons with both fixed ratio and lower limit of normal with a low FEV1 (1.79, p < 0.0001), in those with fixed ratio only with a low FEV1 (1.77, p < 0.0001), in those with abnormal fixed ratio only with a normal FEV1 (1.28, p < 0.0001) compared with persons with no airflow obstruction (reference group). These remained significant after adjusting for demographic variables and other confounding variables. CONCLUSIONS: The addition of FEV1 < 80% of predicted increased the prognostic power of the fixed ratio <0.7 and/or below the lower limit of predicted criteria for airway obstruction.